KARAKTERISTIK AGROINDUSTRI KERIPIK DAN MINIATUR MOBIL-MOBILAN DI DESA SUNGAI LANGKA - Mega Surya Ningsih; M. Bobby Rahman; Baiq Rindang Aprildahani (Jurnal Perencanaan dan Pengembangan Kebijakan, 2022)
Agroindustrial activities have an important role to support the agricultural sector both from an economic and social perspective. This is supported by the superior characteristics possessed by agroindustry, namely the use of raw materials from natural resources available locally. Sungai Langka Village is one of the villages that has agricultural potential that can support the development of agro-industrial areas. The purpose of this study was to determine the characteristics of agro-industry activities in Sungai Langka Village. This research uses descriptive qualitative method which is supported by quantitative method. The results reveals that there are two types of agro-industry activities that developed in Sungai Langka Village, namely chips agro-industry and mini-cars agro-industry. Agroindustry in Sungai Langka Village is dominated by small scale and households, with the highest participation being dominated by men at 89 percent, but it is also inseparable from the contribution of women, the majority of business actors have low to moderate levels of education, and raw materials are mostly obtained from local and a small number of non-local, the scope of marketing has reached national level, and there are several institutions that play a role in the development of agro-industry in Sungai Langka Village such as the government, organizational human initiatives, Bank BRI, and etc